Liver-directed lentiviral gene therapy in a dog model of hemophilia B - Cantore, Alessio; Bartholomä, Cynthia C.; Schmidt, Manfred (Science translational medicine, 2015)
We investigated the efficacy of liver-directed gene therapy using lentiviral vectors in a large animal model of hemophilia B and evaluated the risk of insertional mutagenesis in tumor-prone mouse models. We showed that gene therapy using lentiviral vectors targeting the expression of a canine factor IX transgene in hepatocytes was well tolerated and provided a stable long-term production of coagulation factor IX in dogs with hemophilia B. By exploiting three different mouse models designed to amplify the consequences of insertional mutagenesis, we showed that no genotoxicity was detected with these lentiviral vectors. Our findings suggest that lentiviral vectors may be an attractive candidate for gene therapy targeted to the liver and may be potentially useful for the treatment of hemophilia. Gene therapy with lentiviral vectors targeting transgene expression to hepatocytes provides stable reconstitution of clotting activity in dogs with hemophilia B and does not show genotoxicity in tumor-prone mice. Gene therapy with lentiviral vectors targeting transgene expression to hepatocytes provides stable reconstitution of clotting activity in dogs with hemophilia B and does not show genotoxicity in tumor-prone mice.